A Cross-national Investigation of the Satisfaction and Loyalty Linkage for Mobile Telecommunications Services across Eight Countries. Issue 1 (February 2013) - Aksoy, Lerzan; Buoye, Alexander; Aksoy, Pelin; Larivière, Bart; Keiningham, Timothy L.
Improving customer satisfaction has become a strategic imperative for managers and researchers given the benefits of developing customer loyalty for long-term financial success. Creating these linkages becomes even more important in the context of mobile telecommunications due to the ubiquitous nature of mobile phones and the potential this creates to engage in interactive marketing for firms. Further, with increased global penetration of mobile telecommunications, examining cross-national differences in consumer attitudes and behaviors has become critical. Most studies that examine customer satisfaction and loyalty linkages however have traditionally focused on single countries and/or single industries. This study extends the literature by testing the moderating impact of cultural variables on the impact of satisfaction on loyalty intentions using data from 3, 393 mobile telecommunications customers in Australia, Brazil, Canada, China, France, Spain, UK, and USA. Our findings reveal that the impact of satisfaction on loyalty in the mobile telecommunications context depends on cultural differences. The results demonstrate non-linear threshold effects where managers operating in countries characterized by self-expressionist values will have an easier time creating satisfaction and loyalty with mobile customers compared to those operating in cultures dominated by high survivalist values.